Analisis Structural Equation Modeling Partial Least Square pada Kinerja Pegawai PT. Bank Pembangunan Daerah Jambi - Nurhalizah, Siti; Kholijah, Gusmi; Gusmanely, Z (Universitas Sebelas Maret, 2023)
Human resource management is required to be able to continue to develop themselves in order to have high performance and be able to excel at work. The value of employee performance is important which causes the company to require employee performance to be improved. The object of research conducted at the Head Office of Bank Jambi found that there are employees who have not been able to complete the assigned tasks effectively and efficiently. The purpose of this study was to analyze the direct and indirect effects of competency variables and work discipline on employee performance variables with work motivation variables as intervening variables at Bank Jambi. Based on these problems, the results of the analysis and discussion using SEM-PLS are (1) competence and work discipline have a positive and significant effect on work motivation at Bank Jambi. Work motivation can be explained by competence and work discipline by 65.7% and 34.3% is explained by other variables outside those studied, (2) competence, work discipline, and work motivation have a direct positive and significant effect on the performance of Bank Jambi employees. Employee performance can be explained by competence, work discipline, and work motivation by 72.1% and 27.9% explained by other variables outside the study, and (3) competence and work discipline have a positive and significant indirect effect on employee performance with work motivation as an intervening variable.Keywords: Human resources; competence; work discipline; work motivation; employee performance